1998
DOI: 10.1093/toxsci/46.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen Alters Estrogenic Responses in Vitro: Stimulation of DNA Synthesis in Estrogen-Responsive Human Breast Cancer Cells

Abstract: A limited number of studies have investigated the estrogenic potential of acetaminophen but none has reported its effects on breast cells. Many compounds that alter estrogen-mediated processes in various tissues contain p-phenolic moieties. Acetaminophen is a commonly used analgesic/antipyretic that also contains a p-phenol. This study tested the hypothesis that therapeutic concentrations of acetaminophen alter estrogen-responsive human breast cancer cell DNA synthesis. To this end, a modified E-screen assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The proliferation assay for T47D cells was conducted in the same manner except that the cell density used was 3000 per well and E 2 concentration was 10 n M . The ER‐negative cell line (MDA‐MB‐231; Harnagea‐Theophilus and Miller, 1998 ) maintained in Leibovitz's L‐15 medium containing 10% BFS was used as control. Cells (1500 per well) were seeded onto 96‐well microtitre plates and incubated with 10 n M E 2 and various concentrations of test compounds for 3 days followed by the above MTT measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The proliferation assay for T47D cells was conducted in the same manner except that the cell density used was 3000 per well and E 2 concentration was 10 n M . The ER‐negative cell line (MDA‐MB‐231; Harnagea‐Theophilus and Miller, 1998 ) maintained in Leibovitz's L‐15 medium containing 10% BFS was used as control. Cells (1500 per well) were seeded onto 96‐well microtitre plates and incubated with 10 n M E 2 and various concentrations of test compounds for 3 days followed by the above MTT measurement.…”
Section: Methodsmentioning
confidence: 99%
“…This study tests the hypothesis that APAP will have estrogen-like activity on estrogen-inducible alkaline phosphatase activity in Ishikawa cells. Previous studies demonstrate that APAP has estrogen-like activity in breast cancer cell proliferation studies (Harnagea-Theophilus et al, 1998) and inhibits estrogen-induced vitellogenin production in isolated trout liver cells (Miller et al, 1999). No appreciable interactions between APAP and the estrogen receptor have been found (Harnagea-Theophilus b et al, 1999, Isenhower et al, 1986 and the mechanism by which APAP alters these estrogenic-responses is unclear.…”
Section: Hypothesismentioning
confidence: 99%
“…Previous studies in our laboratory have shown that APAP induced cell proliferation in ER+ MCF-7 breast cancer cells and that antiestrogens inhibit APAP-induced proliferation (Harnagea-Theophilus et al, 1998). It was hypothesized that APAP would have a similar stimulatory effect on estrogen-inducible alkaline phosphatase activity in Ishikawa cells.…”
Section: Acetaminophen Inhibits Basal Alkaline Phosphatase Activity Imentioning
confidence: 99%
See 2 more Smart Citations